Do genre studies need the concept of genre sphere? - Dementyev, Vadim Viktorovich (Жанры речи)
The article discusses the legitimacy and appropriateness of using the concept of genre sphere in modern genre studies, by analogy with other “spheres” used in many modern humanities, for example, in conceptology. The author concludes that the genre sphere objectively exists, but the use of the genre sphere as a concept in genre studies also has objective pros and cons. The paper analyzes the possible composition of the genre sphere: the totality of all speech genres/speechgenre space of a separate national culture in a given period and in dynamics; a separate intra-cultural subculture; a separate age subculture. The genre sphere does not include speech acts, tonalities, styles, strategies and tactics, types, precedent texts, as well as actual linguistic units of different types and levels. The paper focuses on the tasks of the “genre sphere theory” and the tasks of genre studies, the solution of which is facilitated by the use of the concept of the genre sphere: the ordering of ideas about the structure of communicative concepts and in their composition – speech genre, national genre sphere and national culture, genrogenic situations, anthology (encyclopedia, dictionary) of speech genres, typology of speech genres. A separate micro-study deals with the categories, scenarios, etc. of the Russian genre sphere (the significance of the concept of communication, communicative personality, greater and lesser elaboration of individual genres, intra-genre tonalities and values, such as iskrennost’ (≈‘sincerity’), spravedlivost’ (≈‘fairness’), pryamota (≈‘directness’), vezhlivost’ (≈‘politeness’), kompliment (≈‘compliment’)). The arguments “against” the use of the concept of genre sphere in genre studies include the insufficient development of the methodology of genre studies, the absence of new special methods and techniques that would be used in studying the genre sphere, as well as the fact that at the current stage of development of genre studies, this concept is perceived as largely redundant in relation to such actively and successfully developed concepts as the speech-genre picture of the modern era, speech-genre space, and near-genre space of speech.